Slow tourism experiences and mobilities - Fullagar, Simone; Markwell, Kevin; Wilson, Erica (Aspects of tourism, 2012)
This book examines the emerging phenomenon of slow tourism, addressing growing consumer concerns with quality leisure time, environmental and cultural sustainability, as well as the embodied experience of place. Drawing on a range of case studies, it explores how slow tourism encapsulates a range of lifestyle practices, mobilities and ethics.